Adsorption of toxic dye Eosin Y from aqueous solution by clay/carbon composite derived from spent bleaching earth. (22nd September 2020) - Liu, Yongde; Chen, Yao; Shi, Yahui; Wan, Dongjin; Chen, Jing; Xiao, Shuhu
Abstract: The environmentally friendly clay/carbon composite (SBE/C) was prepared by one‐step pyrolysis under N2 atmosphere at 700°C of spent bleaching earth (SBE) from the industrial waste of the refined oil industry. SBE/C was tested to remove anionic dye Eosin Y from aqueous water. The results revealed that SBE/C had larger specific surface area than SBE, and the equilibrium adsorption capacity of SBE/C (11.15 mg/g) was about 3 times than that of SBE (4.04 mg/g). The adsorption process was found to be exothermic and spontaneous. The adsorption capacity of SBE/C was independent on pH (5–12), and exhibits satisfactorily recyclable performance. Combined with characterization analysis, the adsorption mechanism likely includes electrostatic interaction, hydrogen bonding, hydrophobic interaction, halogen bonding, and π‐π interaction. Overall, this exploration of SBE/C might open a window to the design of an efficient and low‐cost adsorbent for Eosin Y dye elimination from wastewater. Practitioner points: The resource utilization of industrial waste SBE was achieved. SBE/C was synthesized and tested to adsorb Eosin Y for the first time. SBE/C had characteristics with porous structure and large surface area. pH had little effect on adsorption capacity of SBE/C for Eosin Y. SBE/C exhibited potential for dye elimination from wastewater. Abstract : Preparation, adsorption mechanism and environmental effect of spent bleaching earth carbon.